The Combination of Cyclin D1 and MRI Parameters Improves Breast Cancer Diagnosis and NACT Efficacy Assessment - Fu, Yufei; Shi, Yizhi; Wang, Zhen; Zhou, Xin (Journal of Medical Biochemistry, 2025)
Objective: The purpose of this study is to evaluate the combined diagnostic performance of Cyclin D1 and magnetic resonance imaging (MRI) parameters in breast cancer (BC), while also assessing their ability to forecast treatment response to neoadjuvant chemotherapy (NACT), so as to provide evidence for individualized treatment strategies.Methods: This study recruited 154 BC patients and 148 healthy women. Peripheral blood Cyclin D1 quantification utilized enzyme-linked immunosorbent assay (ELISA), and CA15-3 and CA27.29 (both tumor markers) measurements were made using automated electrochemiluminescence immunoassay. Magnetic resonance imaging (MRI) was conducted to obtain dynamic contrast-enhanced scans, from which radiomics parameters (PSIER, TSICS, ADC) were derived. Diagnostic accuracy for BC and predictive value for chemotherapy response were evaluated through correlation analysis (Pearson), receiver operating characteristic (ROC) curves, and multivariate regression modeling.Results: Cyclin D1 levels were elevated in BC patients compared to healthy controls and showed a positive connection with CA15-3 and CA27.29 (P
Keywords: Cyclin D1; Magnetic resonance imaging; Breast cancer; Diagnosis; Neoadjuvant chemotherapy